(untitled) (African Multidisciplinary Journal of Research, 2023)
This paper investigates the challenges facing social inclusion efforts in urban live-ability among slum-dwellers around Karen suburb, Nairobi City, Kenya. Urban centers present a complex and dynamic element of the modern landscape. In that regard, there is over 1 billion people dwelling in the slums globally, and the number is expected to grow in the next few decades. However, the rapid urbanization is not commensurate to the urban centers’ ability to provide basic infrastructure such as roads and affordable housing; and basic services like tapped water and sanitation especially to the slum dwellers. Therefore, the slum dwellers have been subjected to extreme social exclusion and consequently growing inequalities that have attracted the attention of scholars, civil society, policy and decision-makers, and the affected citizens. The dystopian situation of social exclusion is more experienced in the urban-slums despite rapid urbanization world over. Urbanization has remained one of the most critical and fundamental forces driving the global economy, and one of the key indicators of economic productivity and economic development level. In that regard, the world cannot give up on urbanization because it is projected that by 2050, more than two-thirds of the global population might be living in the urban areas. Consequently, stakeholders are working hard to influence positively the changing contours of urbanization to achieve social integration and urban live-ability and social inclusion. The target population for this study was the households’ heads, born in the slums, and have been involved in attempts to improve the slum dwellers wellbeing. A mixed research method was used, thus a structured questionnaire was used to collect quantitative data, while for the qualitative method, an interview guide was used to collect data through Focus Discussion Groups. The study had four objectives: to establish the types of social exclusion experienced by dwellers in the slums, investigate the efforts by slum centers to promote social inclusion, determine how the Karen slum dwellers are affected by social exclusion, and to evaluate why the stakeholders’ efforts have not been effective in improving social inclusion in Karen slums. The study established the following: the social exclusion is fueled by poor governance, unfair distribution of resources, and the fact that slum dwellers do not participate in decision making and planning due to exclusion; poor relationship between the slum dwellers and the elites fuel tensions, and finally, inadequate service delivery. The efforts by the slum dwellers to improve their wellbeing bear little fruit due to wrong priorities by the government, lack of land tenure dissuades any long-term investment, the social environment in the slums remains insecure and volatile for business. For the existing opportunities to benefit the slums dwellers, there should be strong partnership between all the stakeholders, infrastructure development, participation and enactment of a strong policy framework.